MdMYBDL1 employed by MdHY5 increases anthocyanin accumulation via repression of MdMYB16/308 in apple. (June 2019) - Liu, Wenjun; Wang, Yicheng; Sun, Jingjing; Jiang, Huiyan; Xu, Haifeng; Wang, Nan; Jiang, Shenghui; Fang, Hongcheng; Zhang, Zongying; Wang, Yan-Ling; Chen, Xuesen
Highlights: A novel apple MYB-like protein, MdMYBDL1, is highly similar to AtMYBD. MdMYBDL1 is a downstream target of MdHY5 and promotes anthocyanin accumulation in response to light. Both MdHY5 and MdMYBDL1 inhibit the expression of MdMYB16/308, which encode anthocyanin inhibitors. Abstract: Light is an important environmental factor affecting plant growth and development. Additionally, HY5 is a central factor that coordinates light signal transduction and regulates the expression of flower color-related genes. However, there are few reports describing the co-regulation of apple fruit coloration by MdHY5 and MYB transcription factors. In this study, we detected a light-inducible gene, MdMYBDL1, which encodes a MYB-like domain and is homologous to AtMYBD in Arabidopsis thaliana . Moreover, we observed that MdHY5 binds to the G-box element of the MdMYBDL1 promoter to upregulate expression. The overexpression of MdMYBDL1 enhanced anthocyanin accumulation in apple calli and inhibited the expression of MdMYB16 and its homolog, MdMYB308 . Furthermore, MdMYB16 can form a dimer with MdMYB308 and functions as a negative regulator of anthocyanin biosynthesis. Interestingly, MdMYB16 and MdMYB308 promoter activities were inhibited by MdMYBDL1 and MdHY5. These findings imply that MdHY5 responds to light signals and functions upstream of different types of MYB transcription factors, ultimately regulating anthocyanin accumulation in apples.